POLITIK HUKUM PENANGGULANGAN TINDAK PIDANA TERHADAP PEDAGANG KAKI LIMA - dwiarti, fitri setiyani (FIAT JUSTISIA, 2014)
abstractThis research aimed to describe the choice of law carried out by Local Government of Bandar Lampung in tackling illegal activities of street vendors in the Bambu Kuning Market. By using normative approach and utilizing secondary data, it could be concluded that use of a means of penal or (law) criminal in a policy is a way to streamline the implementation of the regulation. In addition, it can be concluded that the existence of criminal in a regulation will only be effective if: 1) the criminal is seriously preventing, 2) criminal it does not cause an even more dangerous or harmful than would occur if the criminal is not charged, and 3) no other criminal that can effectively prevent the harm or loss smaller. The provision of criminal sanctions in a regulation serves to prevent the occurrence of crime, and in addition, if a crime has occurred, then the function of criminal provisions is to give deterrent effect to the perpetrators.Â Keywords: Legal Politics, Criminal Law and Street Vendors.